Community health workers improve disease control and medication adherence among patients with diabetes and/or hypertension in Chiapas, Mexico: an observational stepped-wedge study. Issue 1 (15th February 2018) - Newman, Patrick M; Franke, Molly F; Arrieta, Jafet; Carrasco, Hector; Elliott, Patrick; Flores, Hugo; Friedman, Alexandra; Graham, Sophia; Martinez, Luis; Palazuelos, Lindsay; Savage, Kevin; Tymeson, Hayley; et al.
Abstract : Background: Non-communicable diseases (NCDs) contribute greatly to morbidity and mortality in low-income and middle-income countries (LMICs). Community health workers (CHWs) may improve disease control and medication adherence among patients with NCDs in LMICs, but data are lacking. We assessed the impact of a CHW-led intervention on disease control and adherence among patients with diabetes and/or hypertension in Chiapas, Mexico. Methods: We conducted a prospective observational study among adult patients with diabetes and/or hypertension, in the context of a stepped-wedge roll-out of a CHW-led intervention. We measured self-reported adherence to medications, blood pressure and haemoglobin A1c at baseline and every 3 months, timed just prior to expansion of the intervention to a new community. We conducted individual-level mixed effects analyses of study data, adjusting for time and clustering by patient and community. Findings: We analysed 108 patients. The CHW-led intervention was associated with a twofold increase in the odds of disease control (OR 2.04, 95% CI 1.15 to 3.62). It was also associated with optimal adherence assessed by 30-day recall (OR 1.86; 95% CI 1.15 to 3.02) and a positive self-assessment of adherence behaviour (OR 2.29; 95% CI 1.26 to 4.15), but not by 5-day recall. Interpretation: A CHW-led adherence intervention was associated with disease control and adherence among adults with diabetes and/or hypertension. This study supports a role of CHWs in supplementing comprehensive primary care for patients with NCDs in LMICs. Trial registration number: NCT02549495 .